An Analysis of the Attribution of Acts of Private Persons to the State in the European Court of Human Rights - Miray Azaklı Köse (Public and Private International Law Bulletin)
This study examines approach of the European Court of Human Rights’ approach to the issue of attribution, one of the main conditions for establishing state responsibility under international law. The study focuses on the relationship between the law of international responsibility and the law of human rights within the context of attribution. Therefore, the paper explains the pri-mary meaning of attribution under international law and, following a detailed analysis of the Court’s case law, provides a comparative analysis with international law. The Court’s jurisprudence on attribution is divided into two parts: the doctrine of positive obligations and the inter-pretation of the concept of governmental organization, especially in terms of the conduct of state companies. The results indicate that the Court has not adopted lex specialis on attribution, and its judgments largely conform to general international law. The paper outlines in detail the rea-sons for this conclusion and the Court’s application corresponding to certain rules under inter-national law. On the other hand, the Court has refrained from using the term “attribution.” In-stead, the Court has been determining which entities would be regarded as state organs in light of the term “non-governmental organization,” as defined in Article 34 of the Convention. There-fore, the Court’s discomfort with the meaning of “non-governmental organization,” which per-tains to the Convention, has caused the Court to adopt its own interpretation of the term and, in some judgments, to focus on the private entity itself rather than the act claimed to be unlawful.